2010
DOI: 10.1007/s11671-010-9809-5
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Study of Protein–Protein Interactions in the Cytochrome CYP11A1 (P450scc)-Containing Steroid Hydroxylase System

Abstract: Atomic force microscopy (AFM) and photon correlation spectroscopy (PCS) were used for monitoring of the procedure for cytochrome CYP11A1 monomerization in solution without phospholipids. It was shown that the incubation of 100 μM CYP11A1 with 12% Emulgen 913 in 50 mM KP, pH 7.4, for 10 min at T = 22°C leads to dissociation of hemoprotein aggregates to monomers with the monomerization degree of (82 ± 4)%. Following the monomerization procedure, CYP11A1 remained functionally active. AFM was employed to detect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 38 publications
1
29
0
3
Order By: Relevance
“…The accuracy of determining the height of the protein using AFM is ~0.1 nm, which is comparable with the X ray resolution when deter mining the protein structure [8]. The AFM method was previously used to visualize proteins of cyto chrome P450 containing systems and their complexes [9][10][11] and to determine the oligomeric state of pro teins of putidaredoxin reductase and BM3 under vari ous conditions during the AFM measurements [12,13].…”
Section: Introductionmentioning
confidence: 92%
“…The accuracy of determining the height of the protein using AFM is ~0.1 nm, which is comparable with the X ray resolution when deter mining the protein structure [8]. The AFM method was previously used to visualize proteins of cyto chrome P450 containing systems and their complexes [9][10][11] and to determine the oligomeric state of pro teins of putidaredoxin reductase and BM3 under vari ous conditions during the AFM measurements [12,13].…”
Section: Introductionmentioning
confidence: 92%
“…Atomic force microscopy (AFM) is commonly used to visualize proteins and their complexes in near-native conditions. [1][2][3][4] The advantage of an AFM-based molecular detector lies in its ability to detect protein macromolecules and their complexes in single-molecule counting mode. 1 Detection of protein immune complexes in pure solutions has been the subject of a large number of studies, which have shown that the difference between the immune complexes and immobilized antibodies can be determined from the difference in the heights of the objects detected by AFM.…”
Section: Introductionmentioning
confidence: 99%
“…Для этой цели в последнее время разрабатываются новые типы биосенсоров на основе нанотехнологий, в частности, сенсор на основе АСМ [1][2][3][4], оптические нанобиосенсоры [5][6][7][8], нанопроволочные биосенсоры [9,10]. Наибольший интерес для диагностики представляют нанопроволочные биосенсоры (НП-биосенсоры) в связи с тем, что они относятся к классу так называемых безметковых ("label-free") детекторов и позволяют проводить регистрацию макромолекул в режиме реального времени.…”
Section: Introductionunclassified